Changing money : how the digital age is transforming financial services - Gosling, Paul; International Computers Ltd. (London : Bowerdean, 1999)
In this authoritative survey, the latest developments are reviewed and explained in clear, jargon-free terms and future trends predicted. Among the developments examined are smart cards, home banking and multi-media kiosk. Banking, commerce and share trading on the internet are analysed, as is the likely impact on the financial services sector of the increasingly important marriage of mobile phones, personal organisers and the internet. An indispensable reference work for anyone working at any level in the financial services industry, for its customers and for students.
"Sponsored by ICL."
Includes bibliographical references.
rpm 15/08/16
Keywords: Financial services industry; Banks and banking; Electronic commerce; Electronic funds transfers